Analisis Minat Belajar Siswa di SDN JATISARI 2 selama PTMT - Margono, Luthfiyyah; Kowiah, Kowiah (Universitas Negeri Makassar, 2023)
The problem in this study was that SDN JATISARI 2 experienced learning difficulties during PTMT. As a result, PTMT must be implemented to counteract the negative effects of online learning. SDN JATISARI 2 made every effort to implement PTMT effectively even though at that time the facilities and infrastructure were still lacking. This study uses qualitative research methods as its main methodology. The conclusion of this study is that the learning interest of SDN Jatisari 2 Bekasi City students while participating in PTMT based on several standard indicators can be described as follows: the expression of feeling happy is 14.35%, the concentration of attention is 38.8%, participation is 19.3%, and initiative is at 13.2% , and third during the learning process at SDN Jatisari 2 students are enthusiastic in learning because the teacher is more assertive, so that the majority of students are active when learning with limited face-to-face.